(untitled) (Fiep Bulletin - online, 2016)
Introduction: Encephalic Vascular Accident (EVA) is among the diseases that most frequently affect people today, having hemiparesis as one of its most evident sequelas, with agreater impairment of the upper limb that usually has a slower recovery than the lower limb. Constrained induced movement therapy (CIMT) has been considered as an upper paretic limb motor function rehabilitation technique that is effective in the functional improvement of this limb. Objective: to investigatethe effectiveness of constrained induced movement therapy in the treatment of paretic upper limb in patients affected by encephalic vascular accident. Method: This bibliographic review was realized by means of research on articles indexed on Scielo, Bireme databases, Capes periodic publications and Latindex. The key words used were, “encephalic vascular accident”, “upper extremity”, “constrained induced movement therapy” and their synonyms. Publications released between 2009 and 2014 were considered. Results and discussion: 1257 articles were initially found, however only six served the criteria of inclusion. The studies in general showed improvement in motor function, ability and overcome of learned nonuse phenomenon, improving the quality and the quantity of movement in the impaired upper limb. Conclusion: It has been evident that despite the results of the CIMT applied in the traditional and modified modes have been proven positive; there is necessity for further studies in this area